Diversity, Distribution and Domestication of Lguminous Plants in Zamfara State Nigeria (Global Journal of Science Frontier Research, 2020)
The ecosystems of savannas and grasslands, provide habitat of important species, regulate an important part of the Earth's nutrient cycles, and serve many purposes for people. Features of these ecosystems, includes the unique coexistence of tree and grass life forms in savannas. The study therefore described the Diversity, distribution and domestication of leguminous plants in Zamfara state northwest Nigeria. The study tends to expose the variety, division and domestication of leguminous plants such as; crops, trees, grass and shrubs. Multistage random sampling technique was employed for the study four local government areas were selected where 25 farmers in two districts in each LGA were also randomly selected. The result of the study indicated that 49.5% of the respondents said leguminous crops were found to be distributed and domesticated, while 5.9% of the respondents and 5.0% indicated that leguminous shrubs and leguminous grass are also found in the study area.28.7% of the respondents revealed that all types of savanna leguminous plants are found in Zamfara states which are economically important to human life. However, the study suggested requires that government should, Research bodies should explore further the potentials of wild and other leguminous plants for the benefit of our farmers and their livestock.
Keywords: crops; distribution; diversity; domestication grass; leguminous; plants and shrubs